Graphene based surface Plasmon polariton for plasmonic waveguide and devices - Nur, Salman Sadat; Zaman, Kashpia; Sarker, Md. Ashaduzzaman; Zarif, Abrar (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.